Normas para la instalación de tele-consultoríos - Arakane, Rintaro (2009)
In this paper we use basic concepts of Telemedicine applying them to the elaboration of norms that define the procedures to follow when implementing a Telemedicine office as well as during the operation of itself; establishing basic principles of operation in technical and clinical aspects. We also detail the basic components that will be essential for the development of a Telemedicine office, main equipment and their specifications; with the purpose of unifying and establishing the necessary minimum requirements for the implementation of different types of Telemedicine offices.